The dark side of the university’s participation in innovation ecosystems - Daniel, Ana Dias (2022)
The concept of innovation ecosystem is inspired by the literature on ecological systems,where a set of living organismspromote collaborative behaviours to thrive in a specificcommunity. In the case of an innovation ecosystem, it is the firm that has the piv-otal role in the ecosystem, in order to succeedinanever-increasingglobalizedworld, where markets are becoming more and more competitive. [...]